Aplikasi Regresi Berganda untuk Menganalisis Pengaruh Gaya Kepemimpinan, Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan - Willis Puspitasi Sari; Nurhasanah; Eka Safitri, Andin; Lina Mulani Sitio, Sartika (Riau Jurnal Teknik Informatika, 2024)
Employee performance is a key factor in the success of an organization, because high employee productivity can increase operational effectiveness and efficiency. Various elements, such as leadership style, motivation, and work discipline, affect this performance. An effective leadership style can create a conducive work environment, which in turn motivates employees to work optimally. In addition, high motivation drives employees to achieve organizational goals, while good work discipline ensures that each task is carried out efficiently and in accordance with applicable procedures. Therefore, a deep understanding of these factors is essential to designing policies that can improve employee performance and support the achievement of overall organizational goals. This study aims to examine the influence of these three factors on employee performance at PT. Usaha Sarana Medika, using multiple regression analysis and data collected from 60 employees through questionnaires.